2016
DOI: 10.1158/0008-5472.can-15-1793
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 Cleavage Alters Bone Remodeling: Different Outcomes in Breast and Prostate Cancer Skeletal Metastasis

Abstract: Management of bone metastasis remains clinically challenging and requires the identification of new molecular target(s) that can be therapeutically exploited to improve patient outcome. Galectin-3 (Gal-3) has been implicated as a secreted factor that alters the bone tumor microenvironment. Proteolytic cleavage of Gal-3 may also contribute to malignant cellular behaviors, but has not been addressed in cancer metastasis. Here, we report that Gal-3 modulates the osteolytic bone tumor microenvironment in the prese… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 55 publications
3
50
0
Order By: Relevance
“…Depending on the nature and distribution of IgE receptors, different functions might be envisaged. Galectin‐3 is well recognized for its contribution to tumour progression and metastasis development , while galectin‐9 seems to have antiproliferative effects . The trimeric FcεRI(αγ2) showed membranous and cytoplasmic expression in intestinal epithelial cells and a prominent FcεRI α‐chain expression was also found in the Paneth cells of patients with cancer of the proximal colon.…”
Section: Ige Receptor Expression On Immune Cells and Epithelial Cellsmentioning
confidence: 99%
“…Depending on the nature and distribution of IgE receptors, different functions might be envisaged. Galectin‐3 is well recognized for its contribution to tumour progression and metastasis development , while galectin‐9 seems to have antiproliferative effects . The trimeric FcεRI(αγ2) showed membranous and cytoplasmic expression in intestinal epithelial cells and a prominent FcεRI α‐chain expression was also found in the Paneth cells of patients with cancer of the proximal colon.…”
Section: Ige Receptor Expression On Immune Cells and Epithelial Cellsmentioning
confidence: 99%
“…17,19,25 Galectin-3C is unable to induce cell activity 4,21 and has been described as a dominant-negative form of galectin-3, 26,27 since it can inhibit galectin-3-induced angiogenesis, 28 affect galectin-3 maintenance of the glycocalyx barrier function at the ocular surface, 29 suppress the contribution of galectin-3 to plateletinduced COX-2 overexpression in HT29 cells, 30 supress breast cancer in vivo, 27 and attenuate galectin-3-induced osteoclastogenesis. 31 The dominant negative galectin-3C has also been shown to reduce motility and invasion in ovarian cancer cells. 32 So far, the inhibitory functions of galectin-3C have not been investigated with respect to neutrophil activation, but its presence in inflamed/infected human tissue is inferred, based on that galecin-3 increases during inflammation, 33,34 neutrophils release (galectin-3-cleaving) proteases during inflammatory processes 21 and protease-positive bacteria release proteases during infection.…”
Section: Introductionmentioning
confidence: 99%
“…In the bone remodelling process during skeletal metastasis of breast and prostate cancers, secreted intact Galectin-3 could induce osteoclastogenesis, whereas Gal3C could inhibit osteoclast differentiation, indicated that Gal3C may play an opposing role 40 . Gal3C inhibited tumour growth and metastasis in orthotopic nude mouse models of human breast cancer and in a murine model of human multiple myeloma 41, 42 .…”
Section: Introductionmentioning
confidence: 99%